Monitoring of the ice caps area changes on Galindez, Winter and Skua Islands (Argentine Islands, West Antarctica) - I. Savchyn; Ye. Shylo (Ukrainian Antarctic Journal, 2020)
Due to global warming, the glaciers and ice systems of Antarctica and the Antarctic Peninsula have been significantly changing in shape and size in recent decades. Therefore, to control, forecast and prevent such processes, it is necessary to constantly monitor and analyse changes in the basic parameters of glaciers and ice systems. This paper proposes a study of changes in the area of ice caps located on the Galindez, Winter and Skua islands (Argentine Islands, West Antarctica). The study is based on the integration of different spatio-temporal datasets into a single system for retrospective geographical monitoring of changes in the area of Galindez, Winter and Skua islands ice caps. The system for integrating space-time datasets is the UTM coordinate system (zone 20, South). Using transformed archival cartographic materials, as well as recently obtained orthophotos, the boundaries of the glaciers in different periods of research were digitized. Based on the identified boundaries, the significance of changes in the area of island glaciers, as well as the rate of their change during 1935–2019, were determined. Based on the integration of different spatio-temporal datasets into a single system, retrospective-geographical monitoring of changes in ice caps area during 1935–2019 was performed. The ice caps were found to be experiencing systematic decrease in area with average linear rate of decrease from –0.30%/year to –0.37%/year. A detailed analysis of all integrated spatio-temporal data sets including determination of the cause of changes in the area of the Galindez, Winter and Skua islands' ice caps is a promising topic for further research.